Genetic trend in Gir breed - Filho, Kepler Euclides; Silva, Luiz Otávio Campos da; Alves, Rafael Geraldo de Oliveira; Figueiredo, Geraldo Ramos de (Pesquisa Agropecuaria Brasileira, 2000)
The importance of weight and weight gain for beef cattle production is responsible for the great emphasis that is devoted to these traits by breeders of different breeds. However, it is very important to maintain the animal breeding programs under surveillance in order to evaluate the genetic progress obtained by a breed as a whole. Thus, this study had the objective of evaluating the genetic trends for gain up to weaning and for gain from weaning to yearling considering the direct genetic and maternal genetic effects for preweaning gain and genetic direct effect for postweaning gain. The genetic trends were estimated by the regression of the annual average expected progeny differences on birth year of the calf. Positive trends were observed for preweaning gain, genetic direct and maternal genetic effect as well. This tendency was also observed for genetic direct effect for postweaning gain. The regression coefficients were 0.19, 0.06 and 0.026 g day-1, for genetic direct and genetic maternal effects for preweaning gain, and for genetic direct effect for postweaning gain, respectively.
Keywords: Brazil; beef cattle; preweaning gain; postweaning gain; genetic gain